KAJIAN LITERATUR TENTANG PENGARUH JUMLAH UANG BEREDAR DAN NILAI TUKAR TERHADAP INFLASI DI INDONESIA - Roma Uli Maria Br Situmeang; Samuel Revaldo Jeverson Siboro; Olive Katrina Joyanka Sihombing; Bona Vintura Suyana Pandiangan; Fitrawaty (STKIP Subang, 2026)
Inflation is a key macroeconomic indicator reflecting economic stability and public welfare. In Indonesia, controlling inflation remains a primary priority of monetary policy due to its broad impact on purchasing power and national economic growth. This study aims to comprehensively examine the influence of money supply and the rupiah exchange rate on inflation through a systematic literature review. The research applies a descriptive qualitative approach by analyzing various empirical studies and relevant monetary economic theories. The findings reveal that the effect of money supply on inflation remains inconsistent; some studies show a negative relationship when increased liquidity is balanced by production capacity growth, while others indicate a positive correlation as predicted by the quantity theory of money. In contrast, the exchange rate consistently demonstrates a positive and significant effect: rupiah depreciation raises import prices and production costs, which are subsequently passed on to consumer prices. Collectively, both variables jointly determine inflation dynamics. It is concluded that effective inflation control requires coordinated monetary policies, integrating money supply management and exchange rate stabilization to maintain sustainable price stability in Indonesia.